The Role of the Community in Teacher Preparation: Exploring a Different Pathway to Becoming a Teacher - Harfitt, Gary (Frontiers in Education, 2018)
Viewing learning as a social and cultural process the premise of this paper is that learner teachers’ developing expertise should not only reside in the knowledge domains typically established by universities and schools. A crucial knowledge domain that is often overlooked by schools and teacher education institutes (TEIs) is the community beyond the walls of the school classroom and university lecture hall. This paper attends to the question of what constitutes an effective teacher in an era of rapid change and throws light on the process of becoming a twenty-first century educator through examining an innovative curriculum design which has made experiential learning (EL) mandatory for all novice teachers at a TEI in Hong Kong. This challenging curriculum initiative in teacher training has enabled a powerful synergy between the core functions of our teacher-training faculty and the wider community. I seek to present findings that point to real impact on student teachers’ professional development – or their sense of becoming – and also in the way TEIs work within their local communities which are positioned as a powerful knowledge space and knowledge holder in the teacher education process. I will also show how community partners such as non-governmental organisations (NGOs) play a highly significant role in the development of beginning teachers and how they might even be seen as ‘co-educators’ in the complex but compelling process of teacher preparation.